Reliability of Medical History Reporting in Older Adults With and Without Cognitive Impairment. (April 2019) - Curcio, Nicholas; Wilmoth, Kristin; LoBue, Christian; Cullum, C Munro
Background: Clinical diagnosis of cognitive disorders depends on accurate reporting of medical history, yet little is known about the reliability and the validity of such reports, particularly in older patients with and without cognitive impairment. Methods: In 2 studies, we examined the reliability and the validity of reported histories of select medical events in adults with and without cognitive impairment from a large national cohort. Results: Information from subjects (N1  = 3664), obtained from 2 time points, 6 to 12  months apart, was consistent across most medical events, regardless of the diagnostic group (range = 97.6%-100% agreement; Cohen κ range = 0.712-0.945), with few exceptions. Validity analyses (N2  = 382) revealed that 3 of 5 medical events assessed showed substantial agreement between self-report information and clinician diagnosis. Conclusions: These data represent some of the first to demonstrate the reliability and the validity of reported select medical events in older adults with and without cognitive impairment.